Risk factors and possibilities of preventing gastroesophageal reflux disease in school-age children - O.Yu. Belousova; O.L. Slobodianiuk; N.V. Pavlenko; O.B. Hanzii; K.V. Voloshyn (Zaslavsky O.Yu., 2018)
Background. The article presents the main problems of early diagnosis of gastroesophageal reflux disease (GERD) in school-age children, which leads to late detection and initiation of treatment. The purpose of the study was to identify the main risk factors that may predispose the development of this disease, as well as triggers that provoke GERD in school-age children. Knowledge of risk factors can help prevent the formation of GERD in children, and, with timely diagnosis of therapy, reduce the severity of the disease and improve quality of life. Materials and methods. Open comparative study included 98 school-age children (31 girls, 67 boys) aged 6 to 18 years (mean age 14.2 years). Diagnosis of gastroesophageal reflux disease was conducted in accordance with the Order of the Ministry of Health of Ukraine dated January 29, 2013, No. 59 "On Approval of Unified Clinical Protocols for Medical Care of Children with Digestive Disorders". During the comprehensive examination, the identification of possible risk factors was made, for which a detailed history collection was performed: the nature of the child's nutrition and the regularity of the meal were evaluated, as well as the mode of the day, the presence and intensity of physical activity, the presence of chronic stress (psycho-traumatic situations), sleep duration, bad habits, false eating habits. Past medical history also revealed the duration of breastfeeding and the time of supplementary food introduction. Physical examination was also aimed at the detection of so-called symptoms of anxiety - "red flags" that may indicate the presence of complications or organic pathology. Results. In both age groups, boys were dominant; besides, there were significantly more children aged 13-17 years in the group with GERD. Early administration of supplements was revealed in both groups, as well as early artificial/mixed feeding. More than 85 % of children had signs of autonomic dysregulation and concomitant pathology of the upper digestive tract. Interestingly, body mass index met norms in most patients, so this risk factor was not significant. Conclusions. The study has revealed the main risk factors that contribute to the formation of GERD in children of two age groups: 6-12 and 13-17 years, and the relationship between individual risk factors with different forms of GERD was analyzed. Optimization of the primary screening diagnosis of GERD can be achieved by using adapted pediatric GERD questionnaire at the outpatient stage of medical care. It includes not only questions about typical esophageal clinical symptoms, but also extravascular and atypical GERD symptoms. Most of the risk factors and trigger factors are modified, so at the stage of primary care, the control of children's status who are at risk of GERD, timely diagnosis and correction of risk factors, or reflux disorders which occur in the presence of these factors will prevent the development of disease or its severe course that will improve the quality of life of the patient.